Reconstruction of Fulfilling the Rights of Domestic Helpers in Employment Relations as a Form of Respect for Human Rights - Shohib Muslim; Shinta Hadiyantina; Hudriyah Mundzir; Khrisna Hadiwinata; Dina Imam Supaat (Fakultas Hukum Universitas Airlangga, Jalan Dharmawangsa Dalam Selatan, 2024)
Indexed by Scopus